A review on detection of drought stress in tea plants through morphological, physiological, and biochemical approaches - Anjarsari, Intan Ratna Dewi; Suminar, Erni; Wiharti, Nabila Ragil (Kultivasi, 2025)
Tea plants (Camellia sinensis) are important commodities with high economic value, but their production is greatly affected by environmental stresses such as drought and extreme temperatures. Global warming in recent years has led to extreme weather events and an increase in the earth's temperature, which also causes drought. Drought stress is one of the most significant abiotic factors affecting crop productivity. However, despite significant progress, there remains a notable gap in research, particularly the lack of integrated studies that combine morphological, physiological, and biochemical indicators for early and precise detection of drought stress in tea plants. To identify and mitigate the impact of this stress, a comprehensive approach is needed that includes morphological, physiological, and biochemical aspects. The morphological approach includes changes in leaf structure, stomatal size and number, and root growth patterns. From a physiological perspective, plant response to drought can be seen through measurements of transpiration rate, leaf water potential, and photosynthetic capacity. On the biochemical side, the accumulation of compounds such as proline, antioxidant enzymes, and stress-related hormones, such as abscisic acid, plays a crucial role in plant adaptation to drought conditions. This review summarizes the latest findings related to these indicators by analyzing relevant articles published between 2007 and 2024, obtained through reference searches on Google Scholar and academic databases such as Scopus, EBSCO, and Clarivate. The articles were further analyzed using descriptive methods. This review aims to summarize the latest findings related to these indicators and identify the most effective methods for detecting drought stress in tea plants. A deeper understanding of the tea plant's response to drought through these three approaches is expected to provide a solid basis for developing better drought management strategies to maintain tea plant productivity amid increasingly extreme climate change.